The new Oxford handbook of economic geography - Clark, Gordon L.; Gertler, Meric S.; Feldman, Maryann P.; Wójcik, Dariusz, 1972- (Oxford : Oxford University Press, 2018)
Sixty-six leading economists and geographers from around the world investigate the rival theories and perspectives that have sustained the development of economic geography. Building on the success of the hugely influential first edition, this volume offers a radically revised, updated, and broader approach to economic geography.
Global Prospects: The Asian Century? / Michael Berry, Benno Engels -- Behaviour in Context / Gordon L. Clark -- Introduction: Economic Geography in the Twenty-first Century / Gordon L. Clark, Maryann P. Feldman, Meric S. Gertler, Dariusz Wójcik -- Evolutionary Economic Geography / Ron Boschma, Koen Frenken -- Global/National/Comparative Perspectives / Meric S. Gertler -- Economic Growth and Development: Geographic Dimensions / Maryann P. Feldman, Michael Storper -- The Logic of Agglomeration / Gilles Duranton, William Kerr -- The Logic of Production Networks / Henry Wai‐chung Yeung -- Corporate Social Responsibility and Standards / Alexandra Hughes -- Firms in Context: Internal and External Drivers of Success/Innovation / Mercedes Delgado -- Inequality in Advanced Economies / Danny Dorling -- Innovation Highways: Connecting North and South / Anita McGahan, Janice Gross Stein -- How Geography Shapes—and is Shaped by—the Internet / Shane Greenstein, Chris Forman, Avi Goldfarb -- Precarious Work & Winner Take-all Economies / Kendra Strauss -- Talent, Skills and Urban Economies / Richard Florida, Charlotta Mellander -- Immigration and the Politics of Skill / Nichola Lowe, Natasha Iskander -- The Global Financial Networks / Dariusz Wójcik -- / Ashby H.B Monk, Rajiv Sharma -- Financialisation of Everyday Life / Karen Lai -- Regional and Urban Disparities / Amy Glasmeier -- Vulnerable Regions in a Changing Climate / Robin Leichenko -- Carbon Markets / Janelle Knox-Hayes -- Resources & the Emergence of the Periphery / Caitlin McElroy -- Digital Finance / Matthew Zook -- Schumpeterian Customers? How Active Users Co-create Innovations / Gernot Grabher, Oliver Ibert -- Towards New Economic Geographies of Retail Globalisation / Neil M. Coe, Neil Wrigley -- The Geography of the Creative Industries: Theoretical Stocktaking and Empirical Illustration /$
Previous edition: The Oxford handbook of economic geography. 2000.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 30, 2018).
Keywords: Economic geography